Giant borderline mucinouscystadenoma in a woman of 46 years-old. Clinical case - González-Rodríguez, Patricia Alejandra; Rodríguez-Villalobos, Paula Cecilia; Hernández-Albino, Maira Fernanda; Gómez-Aguilar, Dalia L.; Collí-Chan, Alejandro; Narváez-Palacios, Juder; Villalobos Rodríguez, Alejandro Lenin; Cárdenas-Núñez, Rafael Del Carmen; Padrón Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction. Ovarian cysts more than 10 cm in dimension are labeled as giant ovarian cysts. Mucinous cystadenomas have the potential to grow into huge mass and rarely remain undiagnosed till they become giant ovarian cysts, they are incidentally found on routine physical examination. Mucinous tumors constitute of benign 75%, borderline 10% and malignant lesions 15%. Giant ovarian tumors generally pose risk due to their location and pressure effects on surrounding structures. Clinical case. A 46-year-old female patient who comes to the consultation because presents a progressive increase in volume of the abdominal region of more than two years of evolution. She presents with dyspnea, low back pain on walking and constipation. An MRI of the abdomen is requested where the abdominal and pelvic cavity is found occupied by a multilocular tumor measuring 297 x 340 x 198 mm, with thin and fine walls, some with internal septa, the signal intensity within the cystic lesions is variable within the different sequences made, but with characteristics of liquid content; with contrast medium applications there is diffuse reinforcement of the wall of the lesions without observing undulations or papillary projections. Unaltered uterus; the anatomical delimitation of both ovaries is not possible due to the characteristics and size of the lesion. Laboratory studies: were normal. Alterated antigens. Exploratory laparotomy + salpingo-oophorectomy bilateral are performed. A transoperative study of the tumor was carried out, which reported: borderline seromucinous cystadenoma, measuring 44 x 36 x 30 cm and weighing 10,170 kg. Discussion. The differential diagnoses of benign ovarian cysts include dermoid cysts, Brenner cysts, and mucinous cysts. Dermoid cysts are sac-like growths on ovaries containing fat, hair, and other tissue types. Brenner cysts are found incidentally and are solid outgrowths on the ovarian surface. Of all the ovarian tumors, mucinous cystadenomas account for 15-20%. These tumors arise from the ovarian surface epithelium and have smooth inner and outer thin walls.